Empowerment of Kelompok Tani Kerja Pertanian Peternakan Perikanan (K2P3) Fafinesu Village Through Post-Harvest Handling Training of Passocery: Pemberdayaan Kelompok Tani Kerja Pertanian Peternakan Perikanan (K2P3) Desa Fafinesu Melalui Pelatihan Penanganan Pascapanen Buah Markisa - Endah Mulat Satmalawati -; Hyldegardis Naisali; Eduardus Y. Neonbeni; Jefrianus Nino (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Fafinesu Village is one of the villages in Kecamatan Insana tengah, Kabupaten Timor Tengah Utara (TTU) NTT which has been involved in horticulture cultivation, especially passion fruit, on a fairly large land area. Passion fruit plants are cultivated together with other horticulture such as papaya and vegetables (tomatoes and chilies). The large amount of passion fruit harvested by Kelompok Tani Kerja Pertanian Peternakan Perikanan (K2P3) which was formed in 2020 in Fafinesu Village has not been utilized optimally and its economic value is not yet visible. Knowledge of post-harvest handling of passion fruit is not widely known by the public. Passion fruit business opportunities are still quite wide open because of marketing opportunities. However, one of the factors that is an obstacle to developing passion fruit is post-harvest technology which is not yet known to farmers. This community service program aims to increase farmers' knowledge and skills in post-harvest handling of passion fruit in order to increase the economic value of passion fruit. One product that is long-lasting is using a high sugar concentrate, so training was carried out in making an instant passion fruit drink combined with the medicinal rhizome plant (turmeric) to become a traditional turmeric and passion fruit sour drink product. The method used in this activity is practice and assistance in processing passion fruit. Community service was successful thanks to the active participation of farmer groups by producing new passion fruit processing products in the form of traditional instant drinks. The knowledge and skills of farmer groups increase and will ultimately have an impact on increasing production and the economy